Judith S. Kaye in her own words : reflections on life and the law, with selected judicial opinions and articles - Kaye, Judith S., 1938-2016 (Excelsior editions., 2019)
In 1983, Judith S. Kaye (1938-2016) became the first woman appointed to the Court of Appeals, New York's highest court. Ten years later, she became the first woman to be appointed chief judge of the court, and by the time she retired, in 2008, she was the longest-serving chief judge in the court's history. During her long career, she distinguished herself as a lawyer, jurist, reformer, mentor, and colleague, as well as a wife and mother. Bringing together Kaye's own autobiography, completed shortly before her death, as well as selected judicial opinions, articles, and speeches, 'Judith S. Kaye in Her Own Words' makes clear why she left such an enduring mark upon the court, the nation, and all who knew her.